Application of yeast surface display system in expression of recombinant pediocin PA-1 in Saccharomyces cerevisiae - Nguyen, Thu Pham Anh; Nguyen, Thu Thi Minh; Nguyen, Nghia Hieu; Nguyen, Tri Nhan; Dang, Thao Thi Phuong (Folia microbiologica, 2020)
Pediocin PA-1 is a bacteriocin that shows strongly anti-microbial activity against some Gram-positive pathogens such as Listeria monocytogenes, Staphylococcus aureus, and Enterococcus faecalis. With the broad inhibitory spectrum as well as high-temperature stability, pediocin has a potential application in the food preservation and pharmaceutical industry. Pediocin has been studied to express in many heterologous expression systems such as Escherichia coli, Saccharomyces cerevisiae, and Pichia pastoris as a free peptide. Here we showed in this study a new strategy by using yeast surface display system to produce the anchored pediocin PA-1 on the cell surface of Saccharomyces cerevisiae, which could be used directly as a pediocin resource. We had successfully constructed a recombinant S. cerevisiae W303 strain that could express pediocin PA-1 on the cell surface. The pediocin-expressing yeast could inhibit the growth of Shigella boydii and Shigella flexneri, which have never been reported before for pediocin activity. Besides, the pediocin expression level of the recombinant S. cerevisiae strain was also evaluated in three different media: synthetic defined (SD), basic medium (BM), and fermentation medium (FM). BM medium was shown to give the highest production yield of the recombinant yeast (4.75 ± 0.75 g dry cell weight per 1 L of culture) with the ratio number of the pediocin-expressing cells of 93.46 ± 2.45%. Taken together, the results clearly showed that pediocin can be displayed on yeast cell surface as anchored protein. The application of yeast cell surface system enables a new door of pediocin application on either food or feed industries. Graphical abstract.
Keywords: Saccharomyces cerevisiae; Pediocins; rekombinantní fúzní proteiny; Microbial Sensitivity Tests; genetické vektory; Bacteriocins; Fermentation; mikrobiální testy citlivosti; antibakteriální látky; Anti-Bacterial Agents; Bacteria; Genetic Vectors; bakteriociny; fermentace; pediociny; Recombinant Fusion Proteins